Comparing the Video-guided Intubation Skills of Competency and Mastery-trained Staff Physicians - Leanne K. Elliott; Nick Wattie; Jonathan Pirie; Kathy Boutis; Adam Dubrowski; Paul Yielder; Natasha Collia (Simulation in Healthcare: The Journal of the Society for Simulation in Healthcare, 2026)
Introduction: Identifying the most effective simulation training approach for maintaining critical skills among staff physicians is essential, as this can affect patient safety and healthcare costs. While competency-based and mastery-based interventions have been studied independently, their effects on skill retention and transfer have not been directly compared. This prospective cohort study compared mastery-based and competency-based training for video laryngoscopy (VL) skill maintenance among staff physicians. Methods: Each intervention included a presimulation online module and a simulation-based training session differing only in performance standards. The competency group (n=8) followed an instructor-determined standard, while the mastery group (n=8) adhered to a higher Mastery Angoff-established standard. VL skills were assessed pre-, post-, and 6 months later (follow-up) in the mastery group; the competency group was assessed only at follow-up. Follow-up included a retention test (pediatric mannequin) and a transfer test (neonatal task trainer). Performance was evaluated using an 18-item checklist (max score: 36) and procedural time (seconds). Results: The mastery group significantly increased mean VL scores and decreased mean VL time from pretest (score=22.13; time=162.00 s) to post-test (34.38; 71.50 s) [( P